Intelligent Computer Mathematics 9th International Conference, AISC 2008 15th Symposium, Calculemus 2008 7th International Conference, MKM 2008 Birmingham, UK, July 28 - August 1, 2008, Proceedings - Autexier, Serge; Campbell, John; Rubio, Julio; Sorge, Volker; Suzuki, Masakazu; Wiedijk, Freek (Lecture Notes in Artificial Intelligence,, 2008)
This book constitutes the joint refereed proceedings of the 9th International Conference on Artificial Intelligence and Symbolic Computation, AISC 2008, the 15th Symposium on the Integration of Symbolic Computation and Mechanized Reasoning, Calculemus 2008, and the 7th International Conference on Mathematical Knowledge Management, MKM 2008, held in Birmingham, UK, in July/August as CICM 2008, the Conferences on Intelligent Computer Mathematics. The 14 revised full papers for AISC 2008, 10 revised full papers for Calculemus 2008, and 18 revised full papers for MKM 2008, plus 5 invited talks, were carefully reviewed and selected from a total of 81 submissions for a joint presentation in the book. The papers cover different aspects of traditional branches in CS such as computer algebra, theorem proving, and artificial intelligence in general, as well as newly emerging ones such as user interfaces, knowledge management, and theory exploration, thus facilitating the development of integrated mechanized mathematical assistants that will be routinely used by mathematicians, computer scientists, and engineers in their every-day business.